Geothermal battery energy storage. (February 2021) - Green, Sidney; McLennan, John; Panja, Palash; Kitz, Kevin; Allis, Richard; Moore, Joseph
Abstract: The Geothermal Battery Energy Storage concept (GB) has been proposed as a large-scale renewable energy storage method. This is particularly important as solar and wind power are being introduced into electric grids, and economical utility-scale storage has not yet become available to handle the variable nature of solar and wind. The Geothermal Battery Energy Storage concept uses solar radiance to heat water on the surface which is then injected into the earth. This hot water creates a high temperature geothermal reservoir acceptable for conventional geothermal electricity production, or for direct heat applications. Storing hot water underground is not new, the unique feature of the GB is its application to sedimentary basins with formations that are water saturated and exhibit high porosity and high permeability. For certain reservoirs like these, calculations suggest that nearly 100% of the stored heat can practically be recovered, and long-term, even seasonal storage is possible. Several publications presented by the authors on the GB, parametrically identified desirable reservoir characteristics [14, 17, 18]. This is a review of those calculations and the inferred conclusions for a viable GB system. Potential GB system well configurations, injection and production scenarios and ultimate heat recovery for economic value are also noted. Graphical abstract: Image 1 Highlights: A concept to store large amounts of renewable energy daily to seasonally. Reservoir characteristics for a geothermal battery system. The conversion of solar or wind to geothermal electricity. Subsurface sedimentary basin formations for large-scale hot water storage. Solar heat collection to create a high-temperature geothermal reservoir.